Gide's bent : sexuality, politics, writing - Lucey, Michael, 1960- (Ideologies of desire., 1995)
This study investigates the place of sexuality in the writings of Andre Gide. Focusing on his work in the 1920s and 1930s, the years in which Gide wrote most openly about his homosexuality, the text shows how Gide's sexuality reflected his political interests.